Using the Process Approach for teaching English descriptive writing - Nyak Mutia Ismail (English Education Journal, 2016)
This study focused on the application of the Process Approach for teaching English descriptive writing. The purpose of this study was to find out whether this approach would work well for the teaching-learning of EFL descriptive writing by 10th grade students at MAN 1 Takengon. An experimental research method was used for this study. The subjects of this study were 61 students of the 10th grade at MAN 1 Takengon that were divided into an experimental group of 31 students and a control group of 30 students. The experimental group was treated by teaching using the Process Approach. Each group was given a pre-test and a post-test. The pre-test and post-test each consisted of one task which asked them to describe their family and Indonesia, respectively. The data were analyzed using SPSS. Before the data were processed, the normality and the homogeneity of the data were tested. The results of the normality and homogeneity tests showed that the data was normal and homogenous. Based on the t-test results the alternative hypothesis Ha was accepted hence the study concluded that there was a positive improvement in the results for writing a descriptive text from the students taught with the Process Approach.